HLA matching in Asian recipients of kidney grafts from unrelated living or cadaveric donors: the collaborative transplant study - Opelz, Gerhard (Human immunology, 2000)
The success rate of kidney transplants in Asian recipients was reported in the literature to be exceptionally high. This raises the question whether HLA incompatibilities do not elicit allograft rejection in Asians. Asian recipients, 3,721, of kidney transplants from unrelated living or cadaveric donors were analyzed. The transplants were part of the Collaborative Transplant Study database. HLA typing data and clinical follow-up information were provided by the participating centers. The survival rate of cadaver kidney transplants was associated statistically significantly with the number of HLA-DR mismatches (p < 0.01) as well as with the number of HLA-A + B + DR mismatches (p < 0.01). A significant association of HLA mismatches with graft outcome was also found in a subanalysis of cadaver transplants from Asian donors into Asian recipients (p = 0.03). Among transplants from unrelated living donors, both HLA-DR mismatches and HLA-A + B + DR mismatches were associated with graft outcome (p < 0.01). The success rate of 123 grafts with 2 HLA-DR mismatches was a poor 69 +/- 4% at 3 years, suggesting that such transplants should be avoided if possible. Kidney transplants from unrelated donors into Asians benefit from improved HLA compatibility. The results, therefore, suggest that prospective HLA matching strategies for Asian patients should be pursued.
Gesehen am 19.02.2021